GENERALISASI BIMBINGAN KONSELING PRIBADI DAN SOSIAL UNTUK REMAJA DI ERA MILENIAL - Akhmad Ramidi; Ishak Hariyanto (Universitas Islam Negeri Mataram, 2018)
The purpose of this paper is to describe the reality of youth in the millennial era about the challenges of the times or the in?uence of globalization. Threats to adolescents are very complex and how to optimize their strengths and opportunities. In this article try to discuss criminal cases that have occurred since 2014-2017 based on historical facts from the Directorate of Political and Security Statistics Indonesia, it turns out the results of the research are crime data and those who are exposed to crimes continue to increase from years previous. Therefore, the author tries to discuss the role of personal and social counselling as a model for developing or minimizing these crimes. The method used is the literature method and descriptive method. The literature method is the result of someone’s writing from the article and tries to distinguish the results from this article. While the descriptive method is data or results of research from one institution to another. The results of the analysis in this article use a group counselling approach in the view of Alfred Adler and require several stages, namely: a. the stage of forming and maintaining relationships, b. stage of analysis and assessment, c. insight stage and, d. back orientation stage.